IN VITRO ANTIBACTERIAL ACTIVITY ROSEMARY OIL AGAINST ESCHERICHIA COLI ISOLATED FROM CLINICAL SAMPLES IN SYRIA - RABIE, LUBNA; BERAKDAR, NOURA (Innovare Journal of Life Sciences, 2022)
Objective: The aim of this research is to determine the antibacterial activity of rosemary oil against Escherichia coli that causes the urinary tract infection) UTI). Methods: An in vitro study was carried out using the following bacterial strains involved in UTI diseases using well diffusion (WD) testing: E. coli (ATCC 25922) and 25 strains were compiled from Aleppo Hospital. It was from people and has UTI. The antibacterial activity of rosemary oil was determined in the form of inhibition zone using agar WD testing. Results: The obtained results indicated that rosemary oil has an inhibitory effect on E. coli (ATCC 25922) and 10 strains. This study showed that rosemary oil has antibacterial activity. Conclusion: Rosemary oil has shown an antibacterial effect that causes UTIs, so we suggest using this oil in the treatment of UTIs.